A new species of Robertsella Guinot, 1969 (Crustacea: Brachyura: Panopeidae) from the southwestern Atlantic - Tavares, Marcos; Gouvêa, Ariane (Zootaxa, 2013)
A new species of deep-water brachyuran crab, Robertsella meridionalis, from Brazil is described and illustrated. The new species can be easily separated from its northwestern Atlantic counterpart, R. mystica Guinot, 1969, by a suite of carapace and appendage characters. Robertsella mystica is redescribed and illustrated. Putative sound-producing structures in the genus Robertsella are first described.